Communicative Language Teaching in Indonesia: Issues of Theoretical Assumptions and Challenges in the Classroom Practice - Bachrudin Musthafa (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
Abstract: Trying to keep abreast to recent development in ESL pedaÃÂgogy, Indonesian GovernmentÃ¢â¬âin this case Ministry of National EducaÃÂtionÃ¢â¬âhas for the past two decades been trying to reform English instrucÃÂtion at the junior and senior high schools across the country. This article describes the issues surrounding the reform initiative and the response the system has made to address the issues. The existing, problematic conditions are delineated and possible ways for improvement are then put forth.